Extensions of the standard model scalar sector and constraints from ccolliders and cosmology - Vaskonen, Ville (2013)
In this thesis we study the Higgs sector of the Standard Model and compare it to the latest data from the LHC and Tevatron experiments. Then we consider two extensions of the Higgs sector. First we extend the Standard Model Higgs sector with one real SU(2) singlet and then we consider two-Higgs- doublet model and extend also it with one real singlet. In both extensions the singlet scalar is considered as a potential dark matter candidate. We find that the parameter space of the so called two-Higgs-doublet-inert-singlet model includes regions which could provide a dark matter candidate which constitutes significant amount of the total dark matter mass density.